Ten Years of Bioethics on Lošinj - Sertić, Tamara; Jurić, Hrvoje, filozof (2011)
On the occasion of the "round-number" anniversary of the scientific-cultural manifestation The Lošinj Days of Bioethics - which has grown in the past 10 years into a most important bioethical conference in this part of Europe - we will recall the history and prehistory of The Lošinj Days of Bioethics, and present numerical indicators as well as content reviews that speak of the range and extent of The Days. Doing so, we will try to show that The Lošinj Days of Bioethics have played a key role in the development of bioethics in Croatia and South-East Europe, together with networking Croatian and South-East European bioethicists with their colleagues from other parts of Europe and the world, and that they have contributed to the development of the innovative concept of integrative bioethics, which is already recognised in the world bioethical discussion. Due to the fact that the year 2011 marks the 100th birth and 10th death anniversary of Van Rensselaer Potter, regarded as the "father of bioethics", we will use this opportunity also to reminisce on his persona and work, and reproduce the greeting message and the lecture on bioethics in the 21st century, which Potter addressed, in an audio-visual form, just a few months prior to his death, to the international conference "Bioethics and Science in the New Epoch", held in Mali Lošinj in 2001.
Projekt MZOS
ENG